The Diagnostic Role of Serum Inflammatory and Soluble Proteins on Dementia Subtypes: Correlation with Cognitive and Functional Decline - Candan Öztürk; Aynur Özge; Osman Özgür Yalın; İ. Arda Yılmaz; Nuran Delialioglu; Çilem Yıldız; Bahar Tesdelen; Cigdem Kudiaki (Behavioural Neurology)
In the past years, the possible involvement of inflammation in the pathogenesis of dementia has been the subject of several investigations. However there are restricted data about the profile of the inflammatory and soluble proteins in well evaluated Alzheimer’s disease (AD), vascular dementia (VD), mild cognitive impairment (MCI) and healthy controls. There are also no reliable data regarding the relationship between the overlapping protein levels and cognitive or functional decline. We measured levels of IL-1β, IL-2, IL-6, IL-18, TNF-α, β-Amlyloid 1–40 and α1-antichymotrypsin levels in plasma in groups of total 82 subjects with AD, MCI, VD and controls using enzyme-linked immunosorbent assay (ELISA) method. Our study samples showed high levels of proinflammatory cytokine levels (especially IL-18) in all patient groups but only high levels of α1-antichymotrypsine in VD patients compared to controls. There is no significant correlation between the laboratory and clinical variables except for a link between IL-1β and NPI scores of AD. In conclusion, this study yielded evidence of some shared mechanisms underlying AD and VD and thus motivates further studies of inflammatory markers in various types of dementia and MCI.